The Larvacidal Activity of Moringa aloifera Extract Leaf to The Larva’s Aedes aegypti Mortality - Ratna Mustika Yasi; Restiani Sih Harsanti (Journal of Agromedicine and Medical Sciences, 2018)
Dengue Hemorrhagic Fever (DHF) is a disease caused by Dengue virus. The disease is spread rapidly in the territory of Indonesia by Aedes aegypti mosquito as the vector. Using Moringa Aloifera leaf extract as a natural larvacide is an attempt to control the disease. This study aims to determine the effect of Moringa Aloifera leaf extract on the mortality of Aedes aegypti larvae. Moringa Aloifera leaf extract is obtained by maceration. The experimental design was divided into negative control groups containing aquades, positive controls containing abate and sample treatment groups. Phytochemical test and UV-Vis spectroscopic quantitative test to identify active compounds. A total of 20 Aedes aegypti larvae were put into a glass containing a solution of distilled water, abate solution and sample solution. Observations are made every 2 hours for 24 hours. The results showed that Moringa leaf extract solution could kill larvae at LC50 3953.17 ppm and LT50 18.98 hours. The mortality rates of larvae at each concentration were 1000 ppm, 5.25 units / 2 hours; 2000ppm, 5.28 units / 2 hours; 3000ppm, 5.91 units / 2 hours; 4000 ppm, 7.18 units / 2 hours, and 5000 ppm 8.63 units / 2 hours. The results showed that Moringa Aloifera leaf extract can kill Aedes aegypti larvae because they contain alkaloids, tannins and flavonoids.Keywords: larvacide, Moringa, Aedes aegypti larvae